Influence of eating behaviours and psychosocial factors on overweight and obesity among medical students in a public university in Malaysia - Mohd Zulkefli, Nor Afiah; Ismail, Suriani; Mohammad Sapian, Abdul Hakim; R., Simmadorai; Mohd Nasir, Nor Shahida Akhma (Community Health Society Malaysia, 2014)
Background: Obesity and overweight is one of the global health problems nowadays. The number of overweight and obese male and female in Malaysia age 18 years and older has increased from 1996 to 2006. This study aimed to determine the eating behaviours and psychosocial factors influencing the prevalence of overweight and obesity among medical students in a public university in Malaysia. Methods: A cross sectional study was carried out on 211 medical students selected through simple random sampling in 2014. Their body weight and height were measured, and a validated self- administered questionnaire was used to collect information on the Body Mass Index, socio demographic factors, eating behaviours and psychosocial factors. Data was analysed using SPSS version 21. Results: The prevalence of overweight and obesity among respondents was 16.6% and 3.8% respectively. The results indicated that there were signification associations between race (χ2=11.838; p = 0.001), religion (χ2=10.989; p = 0.001), and alcohol consumption (χ2 = 4.641; p = 0.031) with overweight and obesity. Conclusions: Prevalence of overweight and obesity was 20.4%. Race, religion and alcohol consumptions were associated with overweight and obesity. Therefore there is a need to address the influence factors on overweight and obesity among medical students in this public university in Malaysia.